2018
DOI: 10.1109/tbme.2017.2784546
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Field High-Frequency nsPEFs on the Biological Behaviors of Human A375 Melanoma Cells

Abstract: This study investigated the influence of low-field high-frequency nsPEFs on melanoma through evaluating their effects on multiple biological behaviors and is helpful in the treatment of melanoma and other tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…It is important that our data are in quite good agreement with the data of Zhang [32] even he worked on human A375 melanoma cells only. He found that the nsPEFs failed to induce apoptosis of A375 melanoma cells, though it induced necrosis.…”
Section: The Influence Of One or Three Square Impulses With Field Forsupporting
confidence: 86%
“…It is important that our data are in quite good agreement with the data of Zhang [32] even he worked on human A375 melanoma cells only. He found that the nsPEFs failed to induce apoptosis of A375 melanoma cells, though it induced necrosis.…”
Section: The Influence Of One or Three Square Impulses With Field Forsupporting
confidence: 86%
“…Our previous cell and animal experiments using high-frequency nanosecond pulses showed that this pulse form can effectively kill tumor cells and inhibit the growth of tumors in vivo . 16 These findings show that this type of pulse currently has a certain application potential for the treatment of tumors. To some extent, similar to high-frequency microsecond pulses, 3 , 4 , 17 , 18 the muscle contraction arising from high-frequency nanosecond pulses can be reduced by optimizing the pulse parameters.…”
Section: Introductionmentioning
confidence: 81%
“…Compared with ECT and IRE, nsPEFs can have a profound effect on the internal structure of cells due to shorter pulse duration and higher electric field intensity [ 8 , 9 ]. So far, nsPEFs have been tested in vitro and in vivo in a variety of tumors including melanoma [ 10 , 11 ], squamous cell carcinoma [ 12 ], hepatocellular carcinoma [ 13 ], pancreatic cancer [ 14 ], and breast cancer [ 15 ]. Studies have shown that nsPEFs can affect organelles [ 16 ] and plasma membrane [ 17 ], increase intracellular calcium level [ 18 ], induce cell apoptosis [ 19 ], and stimulate the body to produce stress response.…”
Section: Introductionmentioning
confidence: 99%